Dysregulation of the hypothalamus-pituitary-adrenal axis predicts some aspects of the behavioral response to chronic fluoxetine: association with hippocampal cell proliferation - Khemissi, Wahid; Farooq, Rai Khalid; Le Guisquet, Anne-Marie; Sakly, Mohsen; Belzung, Catherine (Frontiers in Behavioral Neuroscience, 2014)
In depressed patients, antidepressant resistance has been associated with dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis but the underlying mechanisms are poorly understood. The scope of this study was to try to create HPA-related antidepressant resistance in mice and to investigate adult hippocampal neurogenesis as a putative mechanism of antidepressant resistance. Mice were subjected to a 9 week Unpredictable Chronic Mild Stress (UCMS). After a 2 weeks drug-free period, mice were segregated in two groups, according to the percentage of corticosterone suppression after dexamethasone injection: High suppression (HS) and Low suppression (LS) mice. From the 5thweek onwards, fluoxetine at a dose of 15 mg/kg (i.p.) was administered daily and at the end of 8th week, a battery of behavioral tests assessing the emotional, cognitive, and motor aspects of UCMS-induced depressive-like behavior was applied. Results show that fluoxetine-induced antidepressant effects were observed with higher amplitude in HS when compared to LS on various behavioral phenotypes, like coat state, novelty suppression of feeding, splash test and nest test. The same profile was found concerning the immunohistochimical analysis of ki-67 positive cells in the dentate gyrus of the hippocampus, which is a marker of neuronal proliferation, but not for doublecortin labelling. This suggests that the failure of fluoxetine to induce antidepressant effects may be associated to the poor ability of the compound to stimulate cell proliferation in the hippocampus.